Influence of advanced-footwear-technology spikes on middle- and long-distance running performance measures in trained runners - Rodrigo-Carranza, V.; Muñoz de la Cruz, V.; Hoogkamer, W. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Two new designs of track spikes have recently emerged: spikes with a compliant and resilient midsole foam (eg, polyether block amide [PEBA]) and spikes that combine such modern foam with a carbon fiber plate. We evaluated the effect of these different spikes on running performance measures for middle- and long-distance track events in trained runners.